Making Life Work : Freedom and Disability in a Community Group Home - Levinson, Jack, 1965- (Book collections on Project MUSE., 2010)
Group homes emerged in the United States in the 1970s as a solution to the failure of the large institutions that, for more than a century, segregated and abused people with intellectual and developmental disabilities. Yet community services have not, for the most part, delivered on the promises of rights, self-determination, and integration made more than thirty years ago, and critics predominantly portray group homes simply as settings of social control. Making Life Work/ is a clear-eyed ethnography of a New York City group home based on more than a year of field research. Jack Levinson show.